Modern weapons and military equipment for issue 4-2015 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Slovakia's new Eva 155 mm SP gun breaks cover Carrier face-off :India and China build up  their naval aviationChina builds mystery midget submarine First production Puma delivered Russia reveals firepower plans with new 57 mm turret design Saab Kockums introduces A 26 SSK to the Asia-Pacific region JPO counters media reports that F-35 cannot dogfight